Professional Waqf 5.0: Penta Helix Strategy and Legal Pluralism in the Digital Era - Nurul Hikmah; Syahid Akhmad Faisol; Dicky Eko Prasetio; Kamaluddin Nurdin Marjunid; Mochamad Ikwan (KRTHA BHAYANGKARA, 2026)
Professional waqf is one type of waqf that has the potential to become a means of improving the welfare of society in Indonesia. The development of digitalization essentially presents opportunities to optimize the implementation of professional waqf in Indonesia. This research aims to analyze the penta helix strategy and legal pluralism in optimizing digital-based professional waqf in Indonesia. This research is normative legal research with the aim of conducting reform-oriented research related to the legal policy of professional waqf in Indonesia. Legal materials were collected, including laws and regulations and other research findings, which were then prescriptively analyzed. The research findings confirm that one of the obstacles to implementing professional waqf in Indonesia is the lack of specific regulations regarding professional waqf, which leads to legal uncertainty in its implementation. Through the legal pluralism approach, the regulation of professional waqf will be more optimal and synergistic with Islamic law and state law. Optimizing professional waqf requires a pentahelix approach involving the community, universities, business actors, government, and the media thru a transparent and participatory digitalization process. Digitalization implemented with a penta helix-based approach and accommodating legal pluralism is expected to increase community participation and contribution to the implementation of professional waqf in Indonesia. The academic contribution of this research lies in the use of the penta helix approach and legal pluralism, where professional waqf not only requires a legal framework in the form of regulations but also needs the penta helix approach and legal pluralism to optimize professional waqf in Indonesia.